The impact of major infectious disease events and government relief packages on the film industry: evidence from Taiwan - Liza Lee; Ying-Sing Liu (Humanities & Social Sciences Communications)
Abstract This study focuses on the impact of COVID-19 on the film industry and the effectiveness of government relief policies. Taiwan was a region with a low level of infection at the beginning of the COVID-19 pandemic (2020), and the film industry could be maintained under government policies; therefore, this case study was conducted. Multiple regression models were used to explore the explanatory factors for movie box offices based on running size, production studios and countries, vacations, and the COVID-19 pandemic. The analysis covered a period from September 30, 2019, to September 27, 2020, encompassing a 52-week sample of 5686 films. The results indicated that weekly box office receipts (number of tickets sold) experienced a steep decline of more than 50% despite the implementation of various relief measures. While the number of locally produced films screened diminished significantly, the number of theatres, films, and rerun films and their market share increased substantially. This suggests that although the quantity of films remained stable during the pandemic, their quality or novelty did not correspondingly improve. Key findings from the regression models included the following: (1) there is a size effect (number of theaters screening the film) on the box office; (2) box offices decrease with the number of weeks since the opening week, and films from well-known producers and major studios, as well as products from the US, Japan, and Taiwan, can have positive effects on the box office; (3) student vacations have had a positive effect; and (4) the COVID-19 pandemic has had a negative effect.